Analisis Faktor Yang Berhubungan Dengan Tingkat Kadar Asam Urat - Dian Faqih; Ainul Yaqin Salam; Grido Handoko Sriyono (Pusat riset dan Inovasi Nasional, 2023)
There are a number of factors that can impact the value of uric acid levels, which can result in increased blood uric acid levels.This study aims to determine variables influencing uric acid levels. This research method used correlational analytic with cross sectional approach. The sampling technique used total sampling of gout respondents with a total sample of 51 responents. The results of this study found that there was a relationship between all the factors stuied, both from diet, age, physical activity and BMI with p value ≥ 0.05, while the dominant factor releted to the level of uric acid levels is the dietary factor with p value = 0.000, a ≥ 0.05 and OR value = 30.664. It can be concluded that diet, age, physical activity and BMI can affect uric acid levels but the most dominan factor in creasing uric acid levels is diet, so that future researchers are expected to provide can examine dietary variables in gout patients and increase the number of samples so that the results of the study are maximized .